MAR550: Basic Navigation / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2023)
This course introduces students to the types of navigation and projection charts as well as the navigational methods. Students are exposed to the application of compass and bearing, knowledge on tidal information, international buoyage system, navigational regulations including navigational procedure. In addition, the skills of using navigational aids will also be taught.